Laying The Foundations: Unpacking The Complex Interplay Between Pre-Reading Skills and Early Childhood Education (Integral Research, 2024)
This study looks at how pre-reading skills, teaching methods, and early childhood education are all connected to how children develop reading abilities. It focuses on important skills like recognizing letters, understanding print, building vocabulary, and learning how to understand what they read. The research shows that teaching and learning these skills is not simple and emphasizes the need for teachers and parents to work together. They can create fun, play-based activities that help children develop the skills they need for reading success throughout their lives. The study also highlights how early education is key to helping children build these skills, with both teaching methods and playful learning experiences playing an important role. Ultimately, it shows how teachers and parents collaborating can create a positive environment that encourages early reading development.
Keywords: Pre-reading skills, early childhood education, alphabet knowledge, phonology awareness, print awareness, counting syllable, clapping syllable, instructional practices, play-based learning, parent- educator collaboration, emergent literacy.